Relationship between videogame dependency and social skills in students of a state educational institution in Lima East - Alave Mamani, Sislay Marcia (2019)
This investigation aimed to measure the significant relation between the addiction to videogames andsocial skills. The sample is composed of 375 teenagers of both sexes on a private school in East Lima,Peru. The instrument used is the Videogame Addiction Test of Marcos and Choliz - 2012 and theScale of Social Skills (SSS) of Goldstein - 1978, adapted in Peru by Tomas (1995). The results reveala weak correlation, negative and significant between the videogames addiction and social skills (rho -132p<0,05). Furthermore it was found a significant relation in the social dimensions: “skills alternativeto the aggression” (rho= -.209;p<0,05) and “skills related to stress” (rho= -.108; p<0,05). Therefore, theconclusion was that, while there’s low levels os videogames addiction, there will be more resourcesto have proper relations, or contrariwise.